2018
DOI: 10.1111/cas.13543
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor 3 signal augments radiation‐induced tumor growth retardation in a murine model

Abstract: Radiotherapy induces anti‐tumor immunity by induction of tumor antigens and damage‐associated molecular patterns (DAMP). DNA, a representative DAMP in radiotherapy, activates the stimulator of interferon genes (STING) pathway which enhances the immune response. However, the immune response does not always parallel the inflammation associated with radiotherapy. This lack of correspondence may, in part, explain the radiation‐resistance of tumors. Additive immunotherapy is expected to revive tumor‐specific CTL fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…LLC cells are also radioresistant and aggressively grow in syngeneic mice. 33 , 34 Figure 5 shows the results of irradiating LLC cells to 4 Gy at a range of magnetic field strengths. A clear relationship is observed between cell survival and field strength; the largest reduction in survival (20%) is observed near 40 G, but an increase in survival of more than 10% is observed for fields less than 20 G.
Figure 5 LLC survival using the gradient coils.
…”
Section: Resultsmentioning
confidence: 99%
“…LLC cells are also radioresistant and aggressively grow in syngeneic mice. 33 , 34 Figure 5 shows the results of irradiating LLC cells to 4 Gy at a range of magnetic field strengths. A clear relationship is observed between cell survival and field strength; the largest reduction in survival (20%) is observed near 40 G, but an increase in survival of more than 10% is observed for fields less than 20 G.
Figure 5 LLC survival using the gradient coils.
…”
Section: Resultsmentioning
confidence: 99%
“…The application of the combination treatment decreases the dosage of administered chemotherapy, thereby reducing the side effects in patients and likely achieving better curative effects 58 . Yoshida et al reported that poly(I:C) treatment induces the proliferation of antigen-specific cytotoxic T-lymphocytes (CTLs) by antigen-presenting dendritic cells in draining lymph nodes, and the combination treatment of poly(I:C) with radiotherapy leads to an efficient infiltration of CTLs into tumors and the induction of relevant chemokine transcripts 59 . Moreover, poly(I:C)-activated tumor-associated macrophages led to the release of TNF-α, which can act on tumor cells and increase radiotherapy sensitivity.…”
Section: Combined Application Of Tlrs With Other Cancer Treatmentsmentioning
confidence: 99%
“…The latter artificially produced, induce several wanted immune responses such as enhanced innate immunity and adaptive Th1 response (Krieg 2007). Polyinosinic–polycytydylic acid (poly:C) known to be the double-stranded RNA, able to act as the ligand of TLR3, was shown to inhibit growth of radioresistant Lewis lung carcinoma in mice, when applied in concern with radiotherapy (Yoshida et al 2018). Poly:C given in vivo epicutaneously into human skin resulted in the activation of PRRs in Langerhans cells and keratinocytes manifested by the induction of IFN-regulatory factor 3 and NF-κB (Tajpara et al 2018).…”
Section: The Role Of Tlr Agonists On Tumor Cells’ Behaviormentioning
confidence: 99%